Analisis Performansi Algoritma Greedy Best First Search dan Dijkstra Pada Aplikasi Pencarian Jalur Pendonor Darah Terdekat - Andro Subagio; Bayu Rahayudi; Mochamad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Indonesian Red Cross (PMI) plays a very important role in providing the information needed by the community. One of the main information needed by the community is the blood supply. To obtain information related to the blood supply at PMI, there is a procedure that must be done in advance by the patient's family ie sending a form and blood sample to a blood bank at the hospital or to the laboratory of the PMI Transfusion and Blood Donor Unit (UTDD) in the City. However, the availability of blood stocks in the PMI UTDD is often not sufficient for blood needs and compulsory family families of patients who should look for blood donors that match the blood type of the patient. This certainly does not make it easy for the patient's family. In addition, families of patients who are in need of blood is also not easy to find blood donors who are located closest to the hospital. The shortest path search has several problems, but the main problem is finding the shortest route, of course, looking for the shortest possible route or path. However, for its implementation, this issue can be expanded more broadly among others to find the minimum cost, etc. In this research will be analyzed the performance of software to find information of the nearest blood donor with two different method, that is method of Greedy Best First Search and Dijkstra, besides analyzing the performance of the algorithm, this research also can know the percentage of similarity of output from searching the closest distance of both algortima , so it can know how many percent level of similarity of both algorithm. The result of the Dijkstra algorithm's order of growth value is better than the Greedy Best First Search method with a value of O (n ^ 2) and the similarity of the results of the two algorithms is 75%.